2022
DOI: 10.3390/biom12020193
|View full text |Cite
|
Sign up to set email alerts
|

Trpm8 Expression in Human and Mouse Castration Resistant Prostate Adenocarcinoma Paves the Way for the Preclinical Development of TRPM8-Based Targeted Therapies

Abstract: Metastatic prostate cancer (mPCa) is one of the leading causes of cancer-related mortality in both the US and Europe. Androgen deprivation is the first-line therapy for mPCa; however, resistance to therapy inevitably occurs and the disease progresses to the castration resistant stage, which is uncurable. A definition of novel targeted therapies is necessary for the establishment of innovative and more effective protocols of personalized oncology. We employed genetically engineered mouse models of PCa and human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…However, using their recommended dilutions, only three of them yielded satisfactory results for our standards. Interestingly, Alomone antibody has been widely used for WB [38][39][40] but, in our conditions, it did not work properly. However, in many of these articles, the antibody dilution was lower than recommended and the reported TRPM8 bands were dubious and/or no full membrane/molecular weight markers were shown, making it difficult to rule out the presence of unspecific bands or crossdetection.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, using their recommended dilutions, only three of them yielded satisfactory results for our standards. Interestingly, Alomone antibody has been widely used for WB [38][39][40] but, in our conditions, it did not work properly. However, in many of these articles, the antibody dilution was lower than recommended and the reported TRPM8 bands were dubious and/or no full membrane/molecular weight markers were shown, making it difficult to rule out the presence of unspecific bands or crossdetection.…”
Section: Discussionmentioning
confidence: 81%
“…In our hands, Alomone, ECM2 and ECM3 did not have enough sensitivity and/or specificity to detect endogenous TRPM8, at least with the conventional conditions we used. There is abundant literature using Alomone antibody for detection of endogenous TRPM8 by ICC and/or IHC in different tissues [39,4448]. However, in many of the published figures, the staining pattern was not consistent with the known restrict-ed expression of TRPM8 [31,49].…”
Section: Discussionmentioning
confidence: 99%
“…However, using their recommended dilutions, only three of them yielded satisfactory results for our standards. Interestingly, the Alomone antibody has been widely used for WB [38][39][40], but in our conditions, it did not work properly. However, in many of these articles, the antibody dilution was lower than recommended, and the reported TRPM8 bands were dubious and/or no full membrane/molecular weight markers were shown, making it difficult to rule out the presence of unspecific bands or cross-detection.…”
Section: Discussionmentioning
confidence: 83%
“…In our hands, Alomone, ECM2 and ECM3 did not have enough sensitivity and/or specificity to detect endogenous TRPM8, at least with the conventional conditions we used. There is abundant literature using Alomone antibody for the detection of endogenous TRPM8 by ICC and/or IHC in different tissues [39,[44][45][46][47][48]. However, in many of the published figures, the staining pattern was not consistent with the known restricted expression of TRPM8 [31,49].…”
Section: Discussionmentioning
confidence: 99%
“…Following that, knocking down TRPM8 channels in osteosarcoma and prostate cancer cell lines increased apoptosis induced by epirubicin, suggesting an enhancement in chemosensitivity ( Wang et al, 2013 ; Liu T. et al, 2018 ). In aggressive prostate cancer cells was demonstrated that the agonist D-3263 significantly improves the pro-apoptotic effect of enzalutamide and docetaxel, antiandrogen and antineoplastic, respectively, used in the treatment of prostate cancer ( Genovesi et al, 2022 ).…”
Section: Therapeutic Potential Of Trpm8 In Cancermentioning
confidence: 99%